THE FORGOTTEN BARONG KEDINGKLING AND LEGONG TOMBOL AS GREEN FACADE INSPIRATION - I Putu Udiyana Wasista; Ni Luh Kadek Resi Kerdiati (Journal of Aesthetics, Design, and Art Management, 2021)
Purpose: The purpose of this research and creation is to answer the issue of preserving Balinesetraditions such as barong kedingkling, legong tombol dance, taru pramana, the need for greenspaces during the pandemic, as well as the implementation of the Bali Provincial Regulation No. 5 of2005, in the form of a green facade module with a Balinese identity.Research methods: The method used is based on a design thinking approach which is dividedinto three stages, namely inspiration, ideation, and implementation.Findings: The green facade has a Balinese identity using the form of the barong kedingklingmodule and the legong tombol dance. The plants used are sourced from taru pramana. This strategyis expected to be able to answer the need for preservation, cultural education, and the application oflocal regulations in a new, more modern way.Implications: Preservation of traditional arts can continue with a strategy that is in line with thetimes. There needs to be a creative exploration in line with technological developments. Traditionalart must be able to be applied flexibly so as not to be eroded by the times.